Microalgal biodiesel: A possible solution for India's energy security - Sharma Y.C.; Singh V. (My University, 2025)
Extreme accession in industrialization and urbanization is responsible for huge demand of fossil fuels which are depleting day by day. Hence, search for renewable energy resource has become a considerable challenge in recent years. Biodiesel has been recognized as an alternative fuel, non-toxic and biodegradable which is capable to replace the diesel fuel. In developing countries such as India, there is crisis of edible oil and the edible oil is imported to accomplish the demand. Based on the outline presented, it is observed that search for biodiesel sources should consider the feedstocks that do not require fertile land, do not compete with food crop, help in reduction of greenhouse gas emission as well as decrease the dependency on other nations. So, recently microalgae have emerged to be very auspicious feedstock for production of biodiesel. The present study deals with the systematic analyses of energy demand and GHG emission statistics of various nations as well as all the steps involved in overall process from algal strain selection to biodiesel production. With these challenges, the solutions in biodiesel production from microalgae were also shown. Though, biodiesel is economically viable, more inquisition as well as technological evolvement is required in this direction. To overcome these problems, policies based on usage of bio fuels derived by various nations which encourage biodiesel production, making them rival of conventional energy sources are needed. © 2016 Elsevier Ltd